Differential impact of some risk factors on trochanteric and cervical hip fractures. Issue 4 (26th August 2014) - Tal, Sari; Gurevich, Alexander; Sagiv, Shaul; Guller, Vladimir
<x xml:space="preserve">Abstract</x> Aim To investigate the potential distinct risk factors associated with trochanteric and cervical hip fractures. Methods Elderly patients aged 65 years and older (n = 1161) were admitted to the orthopedic department with hip fractures during the years 2006–2011. Demographic and clinical data, as well as routine blood tests, were retrieved from the patient electronic medical records. Results Approximately 58% of patients had trochanteric fractures and 42% had cervical fractures. Women were more likely to have trochanteric fractures than men (P = 0.002). Female sex, frailty, falls, diabetes and subnormal calcium, as well as subnormal hemoglobin levels, were significant risk factors for trochanteric fractures (OR 1.39, P = 0.0202, OR 1.36, P = 0.0166, OR 1.49, P = 0.0015, OR 1.33, P = 0.0343, OR 0.68, P = 0.0054, OR 0.70, P = 0.0036, respectively). Patients with Parkinson's disease were at a lower risk for trochanteric fractures (OR 0.6, P = 0.007). Conclusion As there are some differences between risk factors for trochanteric and cervical hip fractures, there is a need for further studies in order to understand the etiology of fractures and to be able to carry out effective preventive efforts. Geriatr Gerontol Int 2015; 15: 443–448.